化简求值:(2X+1)^2(3X-2)-(2X+1)(3X-2)^2-X(2X+1)(2-3X),其中X等于二分之三

来源:百度知道 编辑:UC知道 时间:2024/06/26 05:56:43
帮帮忙啊!!!!!!!!!!!!!!

(2X+1)^2(3X-2)-(2X+1)(3X-2)^2-X(2X+1)(2-3X)
=(2x+1)(3x-2)(2x+1-3x+2+x)
=3(2x+1)(3x-2)
=3(3+1)5/2
=30

(2X+1)^2(3X-2)-(2X+1)(3X-2)^2-X(2X+1)(2-3X) =(2x+1)(3x-2)(2x+1-3x+2+x) =3(2x+1)(3x-2) =3(3+1)5/2 =30

另2x+1=a

3x-2=b

原式=a^2*b-a*b^2+x*a*b

=ab(a-b+x)

=(2x+1)(3x-2)*3

如果代入3/2

结果=30

原式
=(2x+1)(3x-2)(2x+1-3x+2+x)
=3(2x+1)(3x-2)
=3*4*5/2
=30

经化简得:
(2X+1)^2(3X-2)-(2X+1)(3X-2)^2-X(2X+1)(2-3X) = 3*(3x-2)*(2x+1)
右因为 x=2/3 所以
原式=3 * 0* 7/3 =0

(2X+1)²(3X-2)-(2X+1)(3X-2)²
+X(2X+1)(3x-2)
=(2x+1)(3x-2)[(2x+1)-(3x-2)+x]
=3(2x+1)(3x-2)
=3*(2*3/2+1)(3*3/2-2)
=3*4*5/2
=30